2021
DOI: 10.3389/fphar.2021.748021
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Counteracts Enteric Inflammation and Bowel Motor Dysfunctions in a Mouse Model of Alzheimer’s Disease

Abstract: Palmitoylethanolamide (PEA), an endogenous lipid mediator, is emerging as a promising pharmacological agent in multiple neurodegenerative disorders for its anti-inflammatory and neuroprotective properties. However, its effects on enteric inflammation and colonic dysmotility associated with Alzheimer’s disease (AD) are lacking. This study was designed to investigate the beneficial effect of PEA administration in counteracting the enteric inflammation and relieving the bowel motor dysfunctions in an AD mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Most evidence regarding a potential therapeutic effect of PEA in NCDs was gathered from preclinical studies administering the compound to animal models of NCDs ( Table 1B ), including AD ( 20 , 31 , 38 , 46 , 47 , 50 ), Aβ-exposed ( 34 ), middle cerebral artery occlusion (MCAo) ( 24 ), PD ( 39 ), vascular dementia (VaD) ( 36 , 42 ), spared nerve injury (SNI) ( 40 , 41 , 49 ), TBI ( 28 ), Complete Freund's Adjuvant (CFA) ( 51 ), and high-fat diet ( 48 ) models. Despite the evidence of similar methodologies across the reviewed studies, a certain heterogeneity was found in terms of animal type [mice ( 20 , 28 , 31 , 36 , 38 42 , 46 , 48 50 ), rat ( 24 , 34 , 47 , 51 )], period of exposure [from 4 to 5 weeks old to 21 months old), PEA formulation [alone unspecified, PEA ( 31 , 34 , 50 , 51 ); alone micronized, PEAm ( 39 ); alone ultra-micronized, um-PEA ( 20 , 38 , 40 , 41 , 46 , 48 ); combined with oxazoline, PEA-OXA ( 42 , 49 ); combined with luteolin, PEALut ( 24 , 28 , 36 , 47 )], PEA mode of administration [intraperitoneal ( 34 , 40 , 41 , 47 , 49 , 51 ), subcutaneous ( 20 , 31 , 38 ), oral ( 24 ,…”
Section: Resultsmentioning
confidence: 99%
“…Most evidence regarding a potential therapeutic effect of PEA in NCDs was gathered from preclinical studies administering the compound to animal models of NCDs ( Table 1B ), including AD ( 20 , 31 , 38 , 46 , 47 , 50 ), Aβ-exposed ( 34 ), middle cerebral artery occlusion (MCAo) ( 24 ), PD ( 39 ), vascular dementia (VaD) ( 36 , 42 ), spared nerve injury (SNI) ( 40 , 41 , 49 ), TBI ( 28 ), Complete Freund's Adjuvant (CFA) ( 51 ), and high-fat diet ( 48 ) models. Despite the evidence of similar methodologies across the reviewed studies, a certain heterogeneity was found in terms of animal type [mice ( 20 , 28 , 31 , 36 , 38 42 , 46 , 48 50 ), rat ( 24 , 34 , 47 , 51 )], period of exposure [from 4 to 5 weeks old to 21 months old), PEA formulation [alone unspecified, PEA ( 31 , 34 , 50 , 51 ); alone micronized, PEAm ( 39 ); alone ultra-micronized, um-PEA ( 20 , 38 , 40 , 41 , 46 , 48 ); combined with oxazoline, PEA-OXA ( 42 , 49 ); combined with luteolin, PEALut ( 24 , 28 , 36 , 47 )], PEA mode of administration [intraperitoneal ( 34 , 40 , 41 , 47 , 49 , 51 ), subcutaneous ( 20 , 31 , 38 ), oral ( 24 ,…”
Section: Resultsmentioning
confidence: 99%
“…57 The anti-inflammatory actions of PEA in the gut have been extended to intestinal inflammation in mouse models of Alzheimer's disease, radiation injury, and ischemia-reperfusion injury. [126][127][128] Although the actions of PEA are terminated by hydrolysis by FAAH, they are also regulated by N-acylethanolamine-hydrolyzing acid amidase (NAAA). 129 Inhibiting NAAA elevates levels of PEA, while not altering those of AEA.…”
Section: Role Of the Endocannabinoid System In Regulating Intestinal ...mentioning
confidence: 99%
“…Similarly, Palmitoylethanolamide (PEA), a lipid mediator, has proven to counteract intestinal dysmotility associated to AD. Specifically, PEA is able to prevent glial hyperactivation and the enteric deposition of AD-related proteins, with a decreased inflammatory status [ 49 ].…”
Section: The Mgb Axis: Communication Links and Role Of Physical Activ...mentioning
confidence: 99%